The Efforts to Improve Thematic Learning Critical Thinking Skill through Problem Based Learning - Pindi Darma Hutama; Naniek Sulistya Wardani; Intan Permana (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to find out whether the improvement of critical thinking skills in thematic learning can be attempted through Problem Based Learning. Moreover, it also wants to know how is the improvement of critical thinking skills student in thematic learning can be attempted through Problem Based Learning. The subjects of this research were class III students, even semester totaling 20 students. The type of this study was classroom action research (CAR). The model of CAR was spiral-shaped from Kemmis and Robin Mc. Tagget. The procedure of this study was implemented at least two cycles if cycle one was already improved. The observation was used in the data collecting. The study instrument used an observation sheet equipped with a performance appraisal rubric. The analysis data technique used was descriptive comparative technique. The result of the study stated that there was an improvement on critical thinking skills students in the thematic learning that PBL attempted had proven. The improvement of the number of skilled in good critical thinking was 15% in cycle 1, and 40% from the totaling students in cycle 2. The improvement of critical thinking skills in the students grade III in the thematic learning was attempted through PBL with steps of 1) reviewing problems by taking notes, 2) asking 3 energy source problems, 3) reasoning solving 3 problems of energy sources, 4) collecting data of energy sources, 5) analyzing data of energy sources, 6) writing report of the result of solving 3 problems of energy sources, 7) presenting the result of solving the problem of energy sources, 8) evaluating the process of energy sources problem-solving.